Suppose $X$ is a random variable taking values in $\mathbb N_0$ with the memoryless property,i.e., for each pair of number $s,t \in \mathbb N$, $$P(X\geq s+t\mid X>t)=P(X\geq s)$$

Show that a random variable $X$ with values in $\mathbb N_0$ has the memoryless property if and only if $X \sim \text{Geometric}(p)$ of parameter $p=P(X=1)$.

I could show that if $X \sim \text{Geometric}(p)$ (for an arbitrary parameter $p$), then $X$ has the memoryless property. I'll write that part of the answer:

$$P(X\geq s)=\sum_{i=s}^{\infty} P(X=i)$$$$=\sum_{i=s}^{\infty} (1-p)^{i-1}p$$$$=\sum_{i=0}^{\infty} (1-p)^{i-1}p-\sum_{i=0}^{s-1}(1-p)^{i-1}p$$$$=\frac{p}{1-p}(\frac{1}{1-(1-p)}-\frac{1-(1-p)^s}{1-(1-p)})$$$$=(1-p)^{s-1}.$$

Similarly, $$P(X\geq s+t\mid X>t)=\dfrac{P((X\geq s+t)\cap (X>t))}{P(X>t)}$$$$=\dfrac{P(X\geq s+t)}{P(X>t)}.$$ After calculating the probability of the numerator and the probability of the denominator, one can arrive to the same expression $$\dfrac{P(X\geq s+t)}{P(X>t)}=(1-p)^{s-1}.$$

So from here one deduces that the geometric random variable has the memoryless property.

I got stuck trying to show the other implication:

Let $s \in \mathbb N, t=1$, let $E=\{X>1\}$, then $$P(X\geq k+1)=P(X \geq k+1\mid X>1)P(X>1)+P(X\geq k+1 \mid X \leq 1)P(X \leq 1).$$

Since the probability $P(X\geq k+1 \mid X \leq 1)=0$, then $$P(X\geq k+1)=P(X \geq k+1\mid X>1)P(X>1)$$

Using the hypothesis, we have $$P(X \geq k+1)=P(X \geq k+1\mid X>1)P(X>1)=P(X \geq k)P(X>1)$$

I got stuck at that point, I want to conclude that $P(X=k)=(1-p)^{k-1}p$, where $p=P(X=1)$.

I would appreciate some help.


1 Answer 1


We have $$P(X\geq s+t\mid X>t)=P(X\geq s)$$ and $$P(X\geq s+t\mid X>t)=\dfrac{P(X\geq s+t)}{P(X>t)}$$ therefore$$P(X\geq s+t)=P(X\geq s)P(X>t).$$ Summing the last equality once over $s$ then once over $t$ we obtain $$I: \sum_{s=1}^{\infty}P(X\geq s+t)=\sum_{s=1}^{\infty}P(X\geq s)P(X>t)$$ $$II: \sum_{t=1}^{\infty}P(X\geq s+t)=\sum_{t=1}^{\infty}P(X\geq s)P(X>t)$$ Now in $I$ set $t=k$, and set $s=k$ in $II$ so that their left hand side be equal and consequently $$P(X\geq k)\sum_{t=2}^{\infty}P(X\geq t)=P(X\geq k+1)\sum_{t=1}^{\infty}P(X\geq t).$$ Now let $\alpha=\sum_{t=2}^{\infty}P(X\geq t)$ and evaluate for $k=1$ to obtain, $$\alpha=\frac{1-p}{p},$$where $p=P(X=1).$ Therefore $(1-p)P(X\geq k)=P(X\geq k+1)$. Since $P(X\geq 1)=1$ we have that $$P(X\geq k)=(1-p)^{k-1}; k=1,2,...$$ implying that $$P(X=k)=(1-p)^{k-1}-(1-p)^{k}=p(1-p)^{k-1}.$$Therefore $X\sim$ Geometric$(p)$.

  • 1
    $\begingroup$ I know this is a pretty old question and answer, but how would I proceed if instead of $P(X\geq s+t)=P(X\geq s)P(x>t)$ I had $P(X>t)=P(X>s)P(X>t-s)$? $\endgroup$ Aug 3, 2016 at 19:05
  • $\begingroup$ @implicati0n Since the random variable only takes values in $\mathbb N$ we have $P(X \ge s) = P(X > s - 1)$. $\endgroup$
    – Ramanujan
    May 8, 2020 at 22:31

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.